PEMBANGUNAN DAN KETERLIBATAN PEREMPUAN - Sukarniati, Lestari Sukarniati (Universitas Muhammadiyah Magelang, 2005)
Development have the meaning and give the big expectation for resident in expanding nations. But in so many development case in some developing countries process this have caused to woman experience of the marginalization. In the development fact in Indonesia, woman role exactly progressively mount posed at increasing the woman labor force participation larger fro the men job participation level in same range of time.